The use of Some modern managevial accounting methods and models of financial failure and their impact on the continuity of Economic units - Eman Reda Mohammed; Raed Majeed Abd (Journal of Madenat Alelem University College, 2022)
The search aims to shed light on two modern methods of modern management accounting methods namely Kaizen and the value stream. identifying the concepts related to them and measuring the degree of adoption by the economic units researched of the two methods. And applying the Financial Failure Model( Springate) to some economic units and measuring their viability to continuity. And studying the potential relationship between the degree of economic units practicing these two methods and the continuity of those units according to the (Springate) model.      The problem of the research lies in the presence of deficiencies in using modern management accounting methods (KC, VS) and models of financial failure. neglecting their role and their impact on the continuity of economic units. The research was formulated with a number of hypotheses. including economic units using modern management accounting methods, including (VS, KC). The effect and correlation when using modern management accounting methods on the continuity of economic units and sub-hypotheses emerge from them. which is an effect relationship and the correlation between the use of the( KC, VS) method And its impact on the continuity of economic units. There is no statistically significant relationship between the use of modern management accounting methods (VS, KC) by economic units at the sect oral level and the continuity of those units and the occurrence of financial failure of the economic unit according to financial failure models. The research was applied in (7) economic units belonging to the industrial and agricultural sectors.     The research reached a set of conclusions, the most prominent of which was the reasonable use of KC and VS methods at different levels, where the relative weights ranged from 78.7% to 73.2. There is a weak correlation between the use of modern management accounting methods and the dimensions of the impact on the continuity of the economic unit, and that there is a positive effect between the use of modern accounting methods on the economic unit. There is no statistically significant relationship between the use of modern management accounting methods( KC, VS) by economic units at the sect oral level and the continuity of those units and the occurrence of financial failure of the economic unit according to financial failure Models.